The NBA's maximum player salary and the distribution of player rents - Kelly M. Hastings; Frank Stephenson (International Journal of Financial Studies, 2015)
The NBA's 1999 Collective Bargaining Agreement (CBA) included provisions capping individual player pay in addition to team payrolls. This study examines the effect the NBA's maximum player salary on player rents by comparing player pay from the 1997 - 1998 and 2003 - 2004 seasons while controlling for player productivity and other factors related to player pay. The results indicate a large increase in the pay received by teams' second highest and, to a lesser extent, third highest paid players. We interpret this result as evidence that the adoption of the maximum player salary shifted rents from stars to complementary players. We also show that the 1999 CBA's rookie contract provisions reduced salaries of early career players.
Keywords: Z22; 330; NBA; maximum player salary; 1999 collective bargaining agreement; rookie contract